Assessing Methods for Enhanced Recovery of Touch DNA from Fingerprints: A Pilot Study - Saamia, Vira; Yudianto, Ahmad; Nurjayadi, Muktiningsih; Novitasari (HAYATI Journal of Biosciences, 2026)
The rapid advancement of science and technology, particularly in forensic science, has significantly enhanced crime investigation methodologies. One such advancement is the utilization of Scientific Crime Investigation methods, specifically the analysis of touch DNA from fingerprints. This research investigates the efficiency of fingerprint powders and swabbing agents in improving the quality and quantity of touch DNA for forensic applications. Touch DNA, derived from cellular materials like sweat and skin cells, presents a valuable source of genetic material for identification purposes. The study involved experimental analyses using Regular Silk Black Fingerprint Powder and Magnetic Dual-Purpose Powder, coupled with non-ionic detergent surfactants as swabbing agents. DNA samples were collected from volunteers with varying DNA shedding levels, processed, and analyzed using quantitative PCR and capillary electrophoresis. Results indicated that fingerprint powders significantly reduce the quantity and quality of recovered DNA due to DNA damage caused by the powders' chemical composition. Conversely, using non-ionic surfactants like Triton™ X-100 in swabbing improved DNA recovery and stability, leading to more complete DNA profiles. This study underscores the importance of optimizing fingerprint powder formulations and DNA sampling techniques to enhance forensic DNA analysis. The findings advocate for the development of less damaging fingerprint powders and improved DNA extraction protocols to preserve the integrity of touch DNA evidence in forensic investigations.